Characterization of Murine Lung Dendritic Cells Infected with Mycobacterium tuberculosis - Gonzalez-Juarrero, Mercedes (American Society for Microbiology, 2001)
Lung dendritic cells were identified by immunohistochemistry in lung tissue sections from C57BL/6 mice. Following isolation from the lungs using CD11c magnetic beads, the flow cytometric analysis of I-A(b+) and CD11c(+) cells indicated a mixed population of dendritic cells at different stages of maturation, with most expressing an immature phenotype. When cultured for 7 days with recombinant murine granulocyte-macrophage colony-stimulating factor, 99% of cells were CD11c(+) and had a morphology typical of immature dendritic cells. These cells were negative for CD34, CD14, and CD8α antigens but expressed low levels of the myeloid marker F4/80 and moderate levels of MAC3. All expressed high levels of CD11a (LFA-1), CD11b (Mac1), and CD54 antigens, with low levels of class II major histocompatibility complex. Most cells expressed CD80 but only a small percentage of cells were positive for CD40 and CD86. Both overnight and 7-day cultures of lung dendritic cells were able to phagocytose Mycobacterium tuberculosis, and this was associated with the production of interleukin-12 and stimulation of both naïve and immune T cells to produce gamma interferon.